Optimization of routine KRAS mutation PCR‐based testing procedure for rational individualized first‐line‐targeted therapy selection in metastatic colorectal cancer. (6th December 2012) - Chretien, Anne‐Sophie; Harlé, Alexandre; Meyer‐Lefebvre, Magali; Rouyer, Marie; Husson, Marie; Ramacci, Carole; Harter, Valentin; Genin, Pascal; Leroux, Agnès; Merlin, Jean‐Louis
Abstract KRAS mutation detection represents a crucial issue in metastatic colorectal cancer (mCRC). The optimization of KRAS mutation detection delay enabling rational prescription of first‐line treatment in mCRC including anti‐EGFR‐targeted therapy requires robust and rapid molecular biology techniques. Routine analysis of mutations in codons 12 and 13 on 674 paraffin‐embedded tissue specimens of mCRC has been performed for KRAS mutations detection using three molecular biology techniques, that is, high‐resolution melting (HRM), polymerase chain reaction restriction fragment length polymorphism (PCR‐RFLP), and allelic discrimination PCR (TaqMan PCR). Discordant cases were assessed with COBAS 4800 KRAS CE‐IVD assay. Among the 674 tumor specimens, 1.5% (10/674) had excessive DNA degradation and could not be analyzed. KRAS mutations were detected in 38.0% (256/674) of the analysable specimens (82.4% in codon 12 and 17.6% in codon 13). Among 613 specimens in whom all three techniques were used, 12 (2.0%) cases of discordance between the three techniques were observed. 83.3% (10/12) of the discordances were due to PCR‐RFLP as confirmed by COBAS 4800 retrospective analysis. The three techniques were statistically comparable (κ > 0.9; P < 0.001). From these results, optimization of the routine procedure consisted of proceeding to systematic KRAS detection using HRM and TaqMan and PCR‐RFLP in case of discordance and allowed significant decrease in delays. The results showed an excellent correlation between the three techniques. Using HRM and TaqMan warrants high‐quality and rapid‐routine KRAS mutation detection in paraffin‐embedded tumor specimens. The new procedure allowed a significant decrease in delays for reporting results, enabling rational prescription of first‐line‐targeted therapy in mCRC.